2012
DOI: 10.1007/s10943-012-9565-1
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of HIV+ Adolescents’ Spirituality: Will You Pray with Me?

Abstract: The aims of the study were (1) to determine whether adolescents find it acceptable to have physicians explore their spiritual beliefs as part of their medical care, (2) to characterize the role of spirituality and religious beliefs in adolescents with and without HIV, and (3) to examine associations between spirituality/religion and quality of life. Adolescents receiving their medical care at an urban Adolescent Health Clinic completed a study-specific questionnaire about spiritual inquiry by their physician, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…HIV positive teens were more likely to report “God abandoned me,” than HIV negative teens (Bernstein et al 2009; Bernstein et al 2012). The belief HIV was a punishment from God, was associated with poor medication adherence among HIV positive teens (Lyon et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…HIV positive teens were more likely to report “God abandoned me,” than HIV negative teens (Bernstein et al 2009; Bernstein et al 2012). The belief HIV was a punishment from God, was associated with poor medication adherence among HIV positive teens (Lyon et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out with 45 HIVpositive adolescents demonstrated that talking about spirituality and religiosity was a way of strengthening in the fight against the disease. HIV negative participants also believed that, if infected, they would consider it important for their fight against the disease to talk about these issues 17 .…”
Section: Strengthening Of Spirituality and Religiositymentioning
confidence: 99%
“…Bernstein et al (2013) published data from 19 HIV-positive ( M age = 17.8) and 26 HIV-negative adolescents ( M age = 16.7) in which four out of the 45 (9 %) had ever been asked by their doctor about their religious/spiritual beliefs, and only eight (18 %) had ever shared these beliefs with their healthcare provider. Most adolescents (67 %) wanted their provider to ask them about their R/S beliefs during some visits, especially when dealing with death/ dying or chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Most adolescents (67 %) wanted their provider to ask them about their R/S beliefs during some visits, especially when dealing with death/ dying or chronic illness. Moreover, adolescents with HIV were more likely to endorse wanting their doctors to pray with them, having felt “God’s presence,” being “part of a larger force,” and having felt that “God had abandoned them,” as compared to those without HIV (Bernstein et al 2013). In our previous study of 151 urban adolescents with asthma (Cotton et al 2012), many adolescents felt that their provider should be aware of and even address their R/S beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation